Amplification and overexpression of the cyclin D1 gene in head and neck squamous cell carcinoma - Wang, X (1995)
Aims—To determine cyclin D1 gene amplification and expression levels in head and neck squamous cell carcinoma (HNSCC) patients. Methods—Total RNA and genomic DNA were isolated from 40 samples of HNSCC tissue and matched normal tissue and were hybridised with a cyclin D1 cDNA probe. Northern and Southern analyses were used to detect mRNA overexpression and cyclin D1 gene amplification, respectively. Results—15 of the 40 HNSCC samples examined (38%) showed cyclin D1 gene amplification. Of these 15 samples, all 13 from which RNA was available showed increased cyclin D1 expression. Conclusions—HNSCC patients with both amplification and overexpression of the cyclin D1 gene are at greater risk than patients who showed no cyclin D1 gene amplification; amplification and over-expression of the cyclin D1 gene may play an important role in the progression of HNSCC and in clinical outcome.